P=90-2(19)

Simple and best practice solution for P=90-2(19) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for P=90-2(19) equation:


Simplifying
P = 90 + -2(19)

Multiply -2 * 19
P = 90 + -38

Combine like terms: 90 + -38 = 52
P = 52

Solving
P = 52

Solving for variable 'P'.

Move all terms containing P to the left, all other terms to the right.

Simplifying
P = 52

See similar equations:

| F(x)=6(x+8)-3 | | 7r=3r | | 11+2b=15 | | 3s-75=s+15 | | 3=11-2x-3x+5 | | P(19)=90-2(19) | | z+87=2z | | 16+2q=12 | | N=-2+x | | -5=12(6x-2)+7x | | s^2+(4s+3)=y | | P(19)=90-2x | | 15-2/5f=-6 | | 19.2j+3(17.3j+4.57)=3(9.8j-2.38) | | X=-2+n | | 14-(X+8)=8X-3 | | 408=-8(10n+9) | | (5-4i)(2+6i)=0 | | 10=z^2+3z | | 0.33(2x-1)=0.5(3x+1) | | g-62=15 | | 16+24=-5(3x-8) | | 6(2x+1)=2x-6x | | -13s-5+5s=11s+2(-11s-16) | | 312.50=a+.25 | | 3y^2+21y=0 | | n=4+(n+1)(-5) | | 2s=2s+6 | | 4(2x+7)=-30+26 | | 6x+19=63 | | -300=5(8a+4) | | -35x+42=-29x-6 |

Equations solver categories